2020
DOI: 10.1007/s00127-020-01835-7
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood and adolescent risk factors for psychotic depression in a general population birth cohort sample

Abstract: Background and purpose In the group of severe mental disorders, psychotic depression (PD) is essentially under-researched. Knowledge about the risk factors is scarce and this applies especially to early risk factors. Our aim was to study early childhood and adolescent risk factors of PD in a representative birth cohort sample with a follow-up of up to 50 years. Methods The study was carried out using the Northern Finland Birth Cohort 1966 (NFBC 1966). We used non-psychotic depression (NPD) (n = 746), schizophr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Change might be reflected in a newly created dialogue beyond national boundaries with regard to human rights and migration. It will be key to find a sustainable balance between bringing income to the local communities again and protecting fragile ecosystems that just started to recover; this could potentially be accomplished with a future focus on slow tourism and the introduction of more systematic rest periods for fishing ( Conway and Timms, 2010 ; Kroner et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Change might be reflected in a newly created dialogue beyond national boundaries with regard to human rights and migration. It will be key to find a sustainable balance between bringing income to the local communities again and protecting fragile ecosystems that just started to recover; this could potentially be accomplished with a future focus on slow tourism and the introduction of more systematic rest periods for fishing ( Conway and Timms, 2010 ; Kroner et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, previous studies failed to nd many demographic differences among patients with PMD versus those with non-psychotic major depression (NMD) [20]. However, there were some exceptions, with the main nding being that a family history [19,21] of psychosis increased the risk for PMD. Other ndings included that patients with PMD were less likely to be Caucasian [4,14] and have lower educational attainment [4,19] compared with those with NMD.…”
Section: Introductionmentioning
confidence: 99%
“…One study observed more years of education in those with PMD compared with NMD [22]. In terms of early childhood and adolescent risk factors, patients with PMD were signi cantly more likely to report histories of physical or sexual abuse [24] and have lower sports grade in school [21] compared with patients with NMD.…”
Section: Introductionmentioning
confidence: 99%
“…In general, previous studies have failed to find many demographic differences between patients with PMD and those without psychotic features [ 18 ]. However, there have been some exceptions; family history [ 19 , 20 ] of psychosis increased the risk for PMD, and ethnicity [ 4 , 14 ] and educational attainment [ 4 , 19 , 21 ] were correlated with psychotic features in depression patients.…”
Section: Introductionmentioning
confidence: 99%